2019
DOI: 10.3390/molecules24071380
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Silico Evaluation of Bikaverin as a Potent Inhibitor of Human Protein Kinase CK2

Abstract: Protein kinase CK2 is an emerging target for therapeutic intervention in human diseases, particularly in cancer. Inhibitors of this enzyme are currently in clinical trials, indicating the druggability of human CK2. By virtual screening of the ZINC database, we found that the natural compound bikaverin can fit well in the ATP binding site of the target enzyme CK2. By further in vitro evaluation using CK2 holoenzyme, bikaverin turned to be a potent inhibitor with an IC50 value of 1.24 µM. In this work, the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…Additionally, recent studies highlighted the putative anti-cancer and anti-tumor properties of bikaverin-like compounds (Haidar et al 2017, 2019), suggesting potentialities for drugs development and pharmaceutical applications in human health, and consequently strengthening the need to confirm the consistency of bikaverin biosynthesis pathway and its intermediates in various Fusarium strains. Bikaverin has been reported in various Fusarium species (Chelkowski et al 1992), but the only reported biosynthetic route for bikaverin has been extensively and exclusively elucidated in Fusarium fujikuroi (Arndt et al 2015; Wiemann et al 2009; Linnemannstöns et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent studies highlighted the putative anti-cancer and anti-tumor properties of bikaverin-like compounds (Haidar et al 2017, 2019), suggesting potentialities for drugs development and pharmaceutical applications in human health, and consequently strengthening the need to confirm the consistency of bikaverin biosynthesis pathway and its intermediates in various Fusarium strains. Bikaverin has been reported in various Fusarium species (Chelkowski et al 1992), but the only reported biosynthetic route for bikaverin has been extensively and exclusively elucidated in Fusarium fujikuroi (Arndt et al 2015; Wiemann et al 2009; Linnemannstöns et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…To tackle this problem, molecular dynamic studies could be performed for any proposed candidate. Unlike docking, which neglects the flexibility of a protein and regards it as relatively rigid structure, molecular dynamic takes into account the conformational flexibility and atomic-level dynamics of the portions, which play essential roles in protein structure [50]. Since our in-house compound library contains several substances with known ATP-competitive mode of inhibition on other kinases, we decided to first focus on the ATP binding site in our in silico docking model.…”
Section: Discussionmentioning
confidence: 99%
“…UNC3230 was able to inhibit hPIP5K1a kinase activity, but only by 25.4% ( Table 1). As our target enzyme has an ATP binding site, we decided to additionally test some known ATP-competitive protein kinase inhibitors such as bikaverin, emodin, ellagic acid, and TBB [38,[48][49][50]. Best hPIP5K1a inhibition values were determined with emodin and ellagic acid.…”
Section: Evaluation Of Compounds Described As Hpip5k1a Inhibitors Beforementioning
confidence: 99%
“…This enzyme is highly expressed and active in several tumor cells, being responsible for suppressing apoptosis and stimulating cell growth. Both cell viability and cell proliferation were drastically reduced after treatment with 10 µM bikaverin for 24 h in MCF7 cells (human breast adenocarcinoma cell line), A427 (human lung carcinoma cell line) and A431 (human epidermoid carcinoma cell line) (Haidar et al 2019).…”
Section: Introductionmentioning
confidence: 99%